(3dhGeY GdHQbs
(3ChdgG (B:s
(3Ydi eGgh Ydjg Ef TGA Gddg JYGdi hbO cTaJ dc ai gPG GdHGH Yf Yde Ldjd adGReg hWGdH faSc Hg Ydi GdOhGe hGdESJeQGQ MJi JahR HGdeWdhH s
(3BNQgG (B:s
(3hYSi Cf CMTQ ai ReQI GdYdeGA dbhdg Udi Gddg Ydjg hSde ef JTHgg Hbhe agh efge hef cKQ ShGO bhe agh efge hGdMeO ddg QH GdYGdejf Je GdcJGH HMeO Gddg hYhfg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI fGbUI GdChd s
(3MGdI GdfSNI LjOI s
Keywords: (3Gdabg GdESdGejs